The Effect Of Using Ai In Adaptive Learning To Improve Student Learning Outcomes At State Senior High School 7 South Bengkulu - Jezi Mariani; Yenni Fitria; Hermawansa Hermawansa (Jurnal Komputer Indonesia, 2026)
This study aims to determine the effect of the use of Artificial Intelligence (AI) in adaptive learning on student learning outcomes in the Informatics subject of Microsoft Excel material at SMA Negeri 7 Bengkulu Selatan. This study is motivated by the low student learning outcomes and the need to utilize technology as a learning medium that can improve student understanding effectively. The research method used is a quasi-experiment with a pretest-posttest control group design. The research sample amounted to 67 students of grade X consisting of the experimental class and the control class. Data collection techniques were carried out through observation, tests, and documentation. Data were analyzed using Validity Test, Reliability Test, normality test, homogeneity test, and hypothesis testing using Paired Sample t-Test. The results showed that the use of AI in adaptive learning provided a higher increase in learning outcomes compared to conventional learning. The average value of the experimental class increased from 65.60 to 80.44, while the control class increased from 62.69 to 72.06. The results of the hypothesis test show a calculated t value of 12.479, which is greater than the t table of 1.697, with a significance value of 0.001 < 0.05. Thus, H₀ is rejected and Hₐ is accepted. The conclusion of this study is that the use of AI in adaptive learning has a significant effect on improving student learning outcomes. It is recommended that teachers utilize AI as an innovative learning medium and schools support the implementation of AI technology in the learning process.